Pelatihan Model Pembelajaran Kooperatif E-Learning pada Peserta didik di Sekolah Dasar - Syamsinar Syamsinar; Firawati Firawati; Rahman Hafid; Elihami Elihami; Akbar Asikin (LP2M Universitas Muhammadiyah Enrekang, 2020)
E-learning cooperative learning model delivery program in elementary schools. The process of implementing the cooperative learning model of E-learning cooperative learning in elementary schools in increasing student learning activities in Islamic Education lessons in Pinrang Regency; The application of the cooperative learning model through cooperative learning E-learning in elementary schools in Islamic education can improve the learning outcomes of fourth grade students of SDN in Pinrang Regency. The instruments used were observation, tests and documentation. The data were processed by percentage analysis and presented in the form of descriptions and presentations. The application begins with numbering, asking questions, thinking together and answering the application of the E-learning cooperative learning model in elementary school learning about natural sciences, social sciences and local economic activities in elementary school classes in Pinrang Regency to improve student learning outcomes.